Improving the Knowledge of Mothers Who Have Babies About Complete Basic Immunization with Animated Audio Visual Media and Leaflets in Kilmuri District, East Seram Regency - Ria Agustini Simanungkalit (Journal of Health Science Community, 2024)
The main obstacle to the success of infant and child immunization is the low awareness influenced by the level of knowledge of mothers in bringing their babies to be immunized and the absence of a sense of community need for immunization. This study aims to determine the increase in knowledge of mothers who have babies about complete basic immunization with animated audio visual media and leaflets in Kilmuri District, East Seram Regency. The type of analytical research with the type of Pre Experimental Designs, one group pretest and posttest. The population was 47 mothers who had babies, a sample of 47 respondents taken using total sampling. The independent variables are Animated Audio Visual Media and Leaflets and the dependent variable is the mother's knowledge . The research instrument is a questionnaire. Data were analyzed using the t-dependent test. The results showed that most of the respondents' knowledge about complete basic immunization before being given animated audio visual media and leaflets was low, which was 31 respondents (65.9%). And most of the respondents' knowledge about complete basic immunization after being given animated audio visual media and leaflets was high, which was 35 respondents (74.5%). Based on the T-test results table, the sig value (0.000) has a value <0.05. So it can be concluded that Ha is accepted and Ho is rejected, which means that there is an influence of the use of Animated Audio Visual Media and Leaflets in increasing mothers' knowledge about complete basic immunization in Kilmuri District, East Seram Regency. Based on the results of the study, it was concluded that there was an increase in the knowledge of mothers who had babies about complete basic immunization before and after being given animated audio visual media and leaflets.